A follow-up study on the abrasivity of commercially available dentrifices in the Philippines - Bautista, Ma. Carmen Concepcion V.
The objective of this study is to be able to contribute updated information on the degree of abrasivity of the commercially available dentifrices in the Philippines, and to aid the dentist and the patient in proper dentifrice selection. Thirteen dentifrices locally available in the market were tested in terms of abrasivity and four of pumice was used as the reference abrasive. Ten samples of acrylic plates were assigned for each dentifrice group. Abrasivity was measured in terms of weight loss which was computed by weighing the samples before and after brushing with the respective dentifrice under controlled conditions. The results obtained revealed that the tested dentifrices had difference degrees of abrasivity, but could not be categorized into high, medium, and low levels for abrasivity because their values were comparable to each other. The selection of the suitable dentifrice still depends on the individual patient's needs and conditions.